Capital structure construction of UMKM ornamental fish Marketers Raja Ikan Noelbaki - Bau Mau, Ignatia Thomasita; Maria B. Mawarni G. Wutun (Jurnal Ekonomi, 2024)
This research reveals important information related to the capital structure used by ornamental fish MSMEs, Raja Ikan Noelbaki, in running their business. By using a qualitative research model, all information related to capital structure can be extracted. It was found that there are four important components in the capital structure, namely the own capital used by ornamental fish business actors, financial management, asset structure and other sources of funding related to investment. These four components are constructed in a model that can make it easier for readers and other MSME business actors to use this research as a benchmark in running a business according to their respective businesses related to capital structure management.